Analisis Kepuasan Pelanggan Menggunakan Shopee PayLater - Iwan Syahputra Sihombing, Fidelis; Putri Maharani, Qadisa; Cindy Amelia, Fenny; Amelia, Cindy (Jurnal Serambi Ekonomi dan Bisnis, 2024)
ShopeePayLater is a loan feature in the form of a credit limit provided by Shopee. This feature allows users to shop now and pay later in 30-day or 3-month installments. This study aims to analyze customer satisfaction using ShopeePayLater. This study used a survey method with 100 respondents of ShopeePayLater users. The research data were analyzed using descriptive analysis and multiple regression test. The results of the study showed that the factors that influence customer satisfaction using ShopeePayLater are system quality, information quality, usage, and service quality. System quality and information quality have a positive and significant effect on customer satisfaction. Usage has a positive effect on customer satisfaction, but not significant. Service quality has a positive and significant effect on customer satisfaction.